(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
In current research environment and needs, the online database becomes one of the main resources in retrieving latest academic information and knowledge. This is due to reason that its synchronization (latest and frequently updated resources) with the on-going research trends and demands. The online database contains a collection of data, text, numerical, graphical, electronic journals, multimedia products and others. Usability of an online database for students may imply on accessing resources for meeting their assignment, project papers and research requirements. In education needs at the higher institution, students have long been using the database to fit in with their study. Nevertheless, little is known from the past works on the students’ online database usability. A survey is conducted on undergraduate students at Universiti Tenaga Nasional (UNITEN), Malaysia. The aim is to examine the relationships between learnability and efficiency, and usage of the online database among these engineering students. The findings indicate that the UNITEN Library should have an opportunity to improvise their online database with respect to learnability and efficiency factors. The research is carried out through a survey participated with a total of 352 respondents. Findings indicate that, 71.7% used the online database and 28.3% was not. Furthermore, usage relationships were found to be with coefficient \(r=-0.353\) (Learnability) and \(r=-0.382\) (Efficiency). Both of the correlations are significant at 1% significant level. The researcher suggested carrying out a further study to investigate the relationship of learnability, efficiency and inclusive of other factors like the effectiveness of the online database to reflect the usability.